Creep indentation of human hip articular cartilage: comparisons of biphasic finite element/optimization and semi-analytical solutions - Constantinides, Georgios; Athanasiou, Kyriacos A.; Agarwal, Animesh (My University, 1992)
Using the semi-analytical/semi-numerical biphasic creep indentation methodology and a biphasic finite element/optimization procedure with experimental creep data, we obtained three material properties of articular cartilage in eight human hip osteochondral specimens. Close agreement was observed in these properties obtained with the two procedures, even though different boundary conditions are used in the two methods. Furthermore, we used a finite element/optimization procedure on various initial time intervals of the experimental creep curves to determine if it is necessary to use all data points up to equilibrium for successful evaluation of the tissue's material properties. The results suggest that, in the human femoral head, as little as the first 20 minutes of experimental creep may be needed for successful evaluation of the tissue's intrinsic mechanical properties.
Keywords: Biomechanics; Finite element method; Mathematical models; Cartilage